Introduction to chemical reactor analysis - Hayes, R. E. (Robert E.); Mmbaga, J. P. (Boca Raton : CRC Press/Taylor & Francis Group, 2013)
'Preface: It has been about 10 years since the first edition of this book was published, and it is probably appropriate to begin by offering a justification for writing the book initially, and generating a second edition. As noted in the preface to the first edition, there are many good textbooks on chemical reaction engineering in existence. Many of the existing books on chemical reaction engineering are both excellent and comprehensive (Elements of Chemical Reaction Engineering by Scott Fogler and Chemical Reaction Engineering by Octave Levenspiel are both considered classics in the field). However, it can be this very comprehensiveness that may make them confusing to the neophyte. Most books contain material sufficient for several courses on chemical reaction engineering, although in some books the more complex topics are touched on only lightly. Other texts contain a mix of undergraduate and graduate level material, which can also make it difficult for the beginner in this topic to progress easily. This book, therefore, is not meant to be either comprehensive or complete, nor is it intended to offer a guide to reactor appreciation or give detailed historical perspectives. Rather, it is intended to provide an effective introduction to reactor analysis, and contains sufficient material to be covered in two terms of about 35-50-minute lectures each on reactor analysis. At the end of reading this book, and working the problems and examples, the reader should have a good basic knowledge sufficient to perform most of the common reaction engineering calculations that are required for the typical practicing engineer. Chemical kinetics and reactor design probably remain as the engineering specialization that separates the chemical engineer from other types of engineer'--
Includes bibliographical references and index.
Keywords: Chemical reactors -- Analysis; Chemical reactors -- Design